Chemotherapy Drives Tertiary Lymphoid Structures That Correlate with ICI-Responsive TCF1+CD8+ T Cells in Metastatic Ovarian Cancer - Lanickova, Tereza; Hensler, Michal; Kasikova, Lenka; Vosahlikova, Sarka; Angelidou, Artemis; Pasulka, Josef; Griebler, Hannah; Drozenova, Jana; Mojzisova, Katerina; Vankerckhoven, Ann; Laco, Jan; Ryska, Ales; et al. (Clinical cancer research, 2025)
PURPOSE: Patients with high-grade serous ovarian carcinoma (HGSOC) are virtually insensitive to immune checkpoint inhibitors (ICI) employed as standalone therapeutics, at least in part reflecting microenvironmental immunosuppression. Thus, conventional chemotherapeutics and targeted anticancer agents that not only mediate cytotoxic effects but also promote the recruitment of immune effector cells to the HGSOC microenvironment stand out as promising combinatorial partners for ICIs in this oncological indication. EXPERIMENTAL DESIGN: We harnessed a variety of transcriptomic, spatial, and functional assays to characterize the differential impact of neoadjuvant paclitaxel-carboplatin on the immunological configuration of paired primary and metastatic HGSOC biopsies as compared to neoadjuvant chemotherapy (NACT)-naïve HGSOC samples from five independent patient cohorts. RESULTS: We found NACT-driven endoplasmic reticulum stress and calreticulin exposure in metastatic HGSOC lesions culminates with the establishment of a dense immune infiltrate including follicular T cells (TFH cells), a prerequisite for mature tertiary lymphoid structure (TLS) formation. In this context, TLS maturation was associated with an increased intratumoral density of ICI-sensitive TCF1+PD1+ CD8+ T cells over their ICI-insensitive TIM-3+PD1+ counterparts. Consistent with this notion, chemotherapy coupled with a PD1-targeting ICI provided a significant survival benefit over either therapeutic approach in syngeneic models of HGSOC bearing high (but not low) tumor mutational burden. CONCLUSIONS: Altogether, our findings suggest that NACT promotes TLS formation and maturation in HGSOC lesions, de facto preserving an intratumoral ICI-sensitive T-cell phenotype. These observations emphasize the role of rational design, especially relative to the administration schedule, for clinical trials testing chemotherapy plus ICIs in patients with HGSOC. See related commentary by Bravo Melgar and Laoui, p. 10.
Keywords: serózní cystadenokarcinom; Hepatocyte Nuclear Factor 1-alpha; protokoly protinádorové kombinované chemoterapie; stres endoplazmatického retikula; ektopické lymfoidní struktury; CD8-Positive T-Lymphocytes; Paclitaxel; Humans; Tumor Microenvironment; Neoadjuvant Therapy; tumor infiltrující lymfocyty; neoadjuvantní terapie; Antineoplastic Combined Chemotherapy Protocols; Female; CD8-pozitivní T-lymfocyty; Carboplatin; hepatocytární jaderný faktor 1-alfa; Tertiary Lymphoid Structures; ženské pohlaví; Endoplasmic Reticulum Stress; inhibitory kontrolních bodů; Immune Checkpoint Inhibitors; karboplatina; lidé; nádorové mikroprostředí; paclitaxel; Lymphocytes, Tumor-Infiltrating; nádory vaječníků; Ovarian Neoplasms; Cystadenocarcinoma, Serous